Sequence of the Mitochondrial Genome of Lactuca virosa Suggests an Unexpected Role in Lactuca sativa’s Evolution - Fertet, Arnaud; Graindorge, Stéfanie; Koechler, Sandrine; de Boer, Gert-Jan; Guilloteau-Fonteny, Emilie; Gualberto, José M. (Frontiers in Plant Science, 2021)
The involvement of the different Lactuca species in the domestication and diversification of cultivated lettuce is not totally understood. Lactuca serriola is considered as the direct ancestor and the closest relative to Lactuca sativa, while the other wild species that can be crossed with L. sativa, Lactuca virosa and Lactuca saligna, would have just contributed to the latter diversification of cultivated typologies. To contribute to the study of Lactuca evolution, we assembled the mtDNA genomes of nine Lactuca spp. accessions, among them three from L. virosa, whose mtDNA had not been studied so far. Our results unveiled little to no intraspecies variation among Lactuca species, with the exception of L. serriola where the accessions we sequenced diverge significantly from the mtDNA of a L. serriola accession already reported. Furthermore, we found a remarkable phylogenetic closeness between the mtDNA of L. sativa and the mtDNA of L. virosa, contrasting to the L. serriola origin of the nuclear and plastidial genomes. These results suggest that a cross between L. virosa and the ancestor of cultivated lettuce is at the origin of the actual mitochondrial genome of L. sativa.